Model SLA Dan ADT Di Perairan Indonesia Selama Badai Siklon Surigae - Ashari Wicaksono; Nike Ika Nuzula (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2021)
Tropical cyclone does not directly pass through Indonesia. However, the impact of tropical cyclones such as high waves, strong winds can have an impact on coastal areas. Surigae tropical cyclones is one of the which reported to have formed in the Pacific Ocean adjacent to northern Sulawesi strait. This study was conducted by analysis SLA and ADT data to obtain models of dynamical of sea level and anomalies during tropical cyclone Surigae across. Results of models showed that from the analysis of SLA data obtained average 0.1 to 0.2 meters, and for ADT obtained average of 0.9 to 1.1 meter. Models of SLA and ADT showed phenomenon of eddies currents at eastern Philippine bordering the Sulawesi strait. SLA and ADT data provided of sea level change of the tropical cyclone, and usable to ocean current and mesoscale eddies detection.